2022
DOI: 10.1038/s41598-021-00825-2
|View full text |Cite
|
Sign up to set email alerts
|

The hypertriglyceridemic waist phenotype is associated with fatty liver and glycometabolic profiles in overweight and obese adults: a cross-sectional study

Abstract: The present study aimed to distinguish different hypertriglyceridemic waist phenotypes and relevant risks of developing fatty liver and abnormal glycometabolic profiles in overweight/obese adults. A total of 1221 Chinese adults with mean (standard deviation [SD]) age of 37 (9) years, 37.3% males and 62.7% females, body mass index (BMI) of 29.0 (4.0) kg/m2, triglyceride (TG) 2.04 (1.45) mmol/L, and waist circumference (WC) 95.8 (10.7) cm were included and classified into four phenotypes: normal TG & normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…The HTGW phenotype has also been widely accepted in risk assessment or prediction of high visceral fat, 14 metabolic syndrome, 54 and fatty liver. 55 All these results support that the HTGW phenotype is a cost-effective screening tool that can be used in clinical practice and an efficient and effective phenotype that can be used in health management.…”
Section: Discussionsupporting
confidence: 55%
“…The HTGW phenotype has also been widely accepted in risk assessment or prediction of high visceral fat, 14 metabolic syndrome, 54 and fatty liver. 55 All these results support that the HTGW phenotype is a cost-effective screening tool that can be used in clinical practice and an efficient and effective phenotype that can be used in health management.…”
Section: Discussionsupporting
confidence: 55%
“…In the earliest investigation and analysis of 962 children and adolescents aged 6–18 years old by Hosseini et al, it was proposed for the first time that the phenotype of HTGW may be related to NAFLD [ 23 ]. Subsequently, similar findings were observed in two Chinese studies, among which Liu et al specially evaluated 1779 premenopausal and postmenopausal women [ 24 ], while Zhou et al chose overweight/obese people [ 25 ]. Considering that these similar studies had some particularity in population selections and their sample size was relatively small, this study further explored the relationship between HTGW phenotype and NAFLD in the general population on the basis of a larger sample.…”
Section: Discussionsupporting
confidence: 66%
“…All these pieces of evidence suggested that the HTGW phenotype may be an adverse phenotype for metabolic-related diseases. At present, several studies have specifically assessed the association between HTGW phenotype and NAFLD in children and adolescents, premenopausal and postmenopausal women, and overweight/obese people [ 23 – 25 ]. However, the association between HTGW phenotype and the risk of NAFLD in the general population is not clear.…”
Section: Introductionmentioning
confidence: 99%